Compliance with the 24-h movement guidelines and the relationship with anthropometry in Finnish preschoolers: the DAGIS study - Marja H. Leppänen; Carola Ray; Heini Wennman; Christina Alexandrou; Katri Sääksjärvi; Leena Koivusilta; Maijaliisa Erkkola; Eva Roos (BioMed Central, 2022)
Background: Recent 24-h movement guidelines for the early years established recommendations for physical activity (PA), screen time (ST), and sleep. To date, few studies have focused on compliance with meeting the guidelines and their associations with health outcomes. Thus, we aimed to investigate: 1) compliance with the 24-h movement guidelines, and 2) associations between compliance and anthropometry in Finnish preschoolers.Methods: We utilized DAGIS survey data that were collected in 2015-2016 (N = 864). PA was assessed 24 h/day over 7 days using a waist-worn ActiGraph wGT3X-BT accelerometer. ST and sleep were reported by the parents during the same 7 days. Anthropometry was assessed using body mass index (BMI, kg/m(2)) and waist circumference (WC, cm). Children were classified as meeting the guidelines if they averaged >= 180 min/day of PA, which consisted of >= 60 min of moderate-to-vigorous intensity; <= 60 min/day of ST; and 10-13 h/day of sleep. In total, 778 children (51% boys, mean age: 4.7 +/- 0.9 years) were included in the study. The compliance with meeting the 24-h movement guidelines was calculated for each behavior separately and in combinations. Adjusted linear regression analyses were applied to examine associations of compliance with BMI and WC.Results: Children were physically active on average 390 (+/- 46.2) min/day and spent 86 (+/- 25.5) min/day in moderate-to-vigorous PA. They spent 76 (+/- 37.4) min/day on ST and had on average 10:21 (+/- 0:33) h:min/day of sleep. The compliance rate in meeting all three movement guidelines overall was 24%. The highest compliance rate was found for PA (85%), followed by sleep (76%) and ST (35%). Meeting guidelines separately for PA or sleep, or for both, were associated with lower WC (PA: B = -1.37, p < 0.001; Sleep: B = -0.72, p = 0.009; PA + Sleep: B = -1.03, p < 0.001). In addition, meeting guidelines for sleep or for both PA and sleep were associated with lower BMI (Sleep: B = -0.26, p = 0.027; PA + Sleep: B = -0.30, p = 0.007). There were no significant associations found regarding ST.Conclusions: Meeting recommendations for PA and sleep may have an important role in supporting a healthy weight status in young children. However, there is still a need to improve compliance with the 24-h movement guidelines, especially for ST.